Evaluation of the opinions of the parents with disabled and healthy children about third hand smoke - Köksoy, Serkan; Can, Belkıs (Journal of Dependence, 2023)
Objective: The objectives of this study were to assess the opinions of parents with disabled children (PDC) and parents with healthy children (PHC) about thirdhand smoke (THS). Method: This study was designed as a cross-sectional study. Study data were collected from the province of Burdur between October and November 2022. Data collection form consists of sociodemographic form, Beliefs about Thirdhand Smoke Scale (BATHS) and Fagerström Test for Nicotine Dependence (FTND). Results: Totally 365 (100%) people participated in the study, 99 (27.1%) of which were PDC and 266 (72.9%) of which were PHC. A statistical difference was found between the BATHS health and BATHS persistence means of PDC and PHC. The existence of rules about not smoking in the environment they live in was in a way that there is a rule for 62 (63%) people, partially there is a rule for 10 (10%) people and no rule for 27 (27%) people for the PDC. For the PHC, it was 138 (51.9%), 43 (16.2%), and 85 (31.9%) (respectively). Conclusion: The means of BATHS health and BATHS persistence in PDC were lower than the mean of PHC. In the whole population; BATHS (including its sub-dimensions) scores were associated with participants’ economic and educational status. More than half of the population had rules prohibiting tobacco use in their residence. The existence of these rules was higher in PDC. In particular, the opinions of the PDC on THS should be intervened with basic public health approaches and they should be provided with sufficient information on the subject.